2004
DOI: 10.1111/j.0300-9475.2004.01364.x
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Inhibitory Amino Acid for Epitope Peptide Binding onto Major Histocompatibility Complex Class II Molecules Enhances Immunogenicity of the Antigen

Abstract: Previously, the arginine at hen egg-white lysozyme 61 (HEL 61) was characterized as inhibiting T-lymphocyte stimulation due to the inefficient binding of the arginine-containing epitope peptide to the corresponding major histocompatibility complex class II molecules in C57BL/6 mice. In this study, we produced recombinant HEL, with arginine or alanine at HEL 61, and compared its ability to induce immune responses in mice to see whether modification of an inhibitory amino acid could enhance the immunogenicity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 51 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…We have previously shown that the crypticity of this epitope is attributable in part to the hindering amino acid residue (arginine, R) at position 61 (R61) [25]. This hindrance can be overcome by the deletion of R61 from peptide 46‐61 [25], by the substitution of R61 within HEL with an alanine residue [45] or by the use of phosphorylated HEL as the immunogen [46]. We suggest that the observed reversal of crypticity of 46‐61 in this study might involve one or more of the following: (1) fine processing of the epitope 46‐61 such that R61 is efficiently removed from the naturally processed epitope; (2) cleavage of the determinant region at a site slightly distal from R61 such that the extended C‐terminal residues could circumvent the hindrance caused by R61; and (3) the immune enhancing effects of cytokines on the APC (on Ii chain, co‐stimulatory molecules, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the crypticity of this epitope is attributable in part to the hindering amino acid residue (arginine, R) at position 61 (R61) [25]. This hindrance can be overcome by the deletion of R61 from peptide 46‐61 [25], by the substitution of R61 within HEL with an alanine residue [45] or by the use of phosphorylated HEL as the immunogen [46]. We suggest that the observed reversal of crypticity of 46‐61 in this study might involve one or more of the following: (1) fine processing of the epitope 46‐61 such that R61 is efficiently removed from the naturally processed epitope; (2) cleavage of the determinant region at a site slightly distal from R61 such that the extended C‐terminal residues could circumvent the hindrance caused by R61; and (3) the immune enhancing effects of cytokines on the APC (on Ii chain, co‐stimulatory molecules, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…The epitope peptides were initially separated using high‐performance liquid chromatography (HPLC; Agilent Technologies, Boeblingen, Germany), and the peptide content and fragmentation of each peak were analysed using Agilent 1100 series LC/MSD Trap ion‐trap mass spectrometer coupled to an Agilent 1100 capillary LC system (Agilent Technologies). The LC system was operated with the electrospray ionization source in positive mode as previously described 16 …”
Section: Methodsmentioning
confidence: 99%
“…To analyse the peptides generated after antigen processing, splenocytes (5 · 10 8 ) from B6 mice were incubated with 250 lg of HEL or PC-HEL in 500 ll of medium for 8 hr at 37°to allow antigen processing as described previously. 16 The splenocytes were initially washed with PBS and then surface-bound processed peptides were eluted with 0Á75 M NaCl for 10 min at room temperature without cell lysis. The supernatant was then concentrated using a YM-3 Amicon concentrator (Millipore Co., Bedford, MA).…”
Section: Mass Spectrometric Analysis Of Apc-bound Hel Peptides Followmentioning
confidence: 99%
See 1 more Smart Citation